Development of PSF/APTES-nano-MCM-48 Mixed Matrix Membrane for CO2/CH4 Separation - Murugiah, Pannir Selvam (Universiti Teknologi PETRONAS, 2016)
The incorporation of inorganic fillers into polymer matrix forms mixed matrix membrane (MMM). Generally, due to the low hydrophobicity of inorganic fillers, undesirable voids are formed on the polymer-inorganic interface, which affects the gas separation performance of the MMMs. In addition to that, the trace addition of nanosized inorganic fillers reported to have smaller inter-particle free-space length compared to micro-sized inorganic fillers on polymer matrix. Thus, this project focused on MMM fabrication using polysulfone (PSf) and functionalized-nano-MCM48 as the polymer matrix and inorganic filler respectively to separate CO2 from CH4. Nano-sized MCM-48 particles was synthesized via modified Stöber method and further functionalized with 3-aminopropyltriethoxysilane (APTES) via post synthesis grafting method to increase its surface hydrophobicity.